2016
DOI: 10.1108/imr-04-2014-0120
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in international marketing: review, assessment, and future research

Abstract: Purpose:Although Corporate Social Responsibility (CSR) has been an issue of major concern for marketers for more than half a century, only recently has it attracted the attention of international marketing researchers. During the last two decades, this body of research has experienced an increasing trend, which, however, is very fragmented and diverse. In response, this article aims to review, assess, and synthesize extant research on the role of CSR activities in international marketing.Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 186 publications
1
65
0
Order By: Relevance
“…CSR refers to an individual's conscious choice to make consumption decisions based on his/her individual moral beliefs. It is also defined as “the application of instrumental, relational, and moral logic by an individual, group, and corporate and institutional agents seeking to influence a broad range of consumer‐oriented responsibilities” (Eteokleous, Leonidou && Katsikeas, 2). CSR not only focuses on avoiding harm to society, but also on acting proactively for the collective social benefit in all stages and aspects of consumption (Baron, ; Nicola Sneddon, Soutar, & Ann Lee, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…CSR refers to an individual's conscious choice to make consumption decisions based on his/her individual moral beliefs. It is also defined as “the application of instrumental, relational, and moral logic by an individual, group, and corporate and institutional agents seeking to influence a broad range of consumer‐oriented responsibilities” (Eteokleous, Leonidou && Katsikeas, 2). CSR not only focuses on avoiding harm to society, but also on acting proactively for the collective social benefit in all stages and aspects of consumption (Baron, ; Nicola Sneddon, Soutar, & Ann Lee, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate Social Responsibility has been studied extensively in the literature of management (McWilliams & Siegel, ; Marquis, Toffel, & Zhou, ; Dowell & Muthulingam, ), operations (Kleindorfer, Singhal, & Wassenhove, ; Liu, Woolley, & Cruz, ; Lee, Nunez, & Cruz, ) and marketing (Sen & Bhattacharya, ; Bhattacharya, ; Eteokleous, Leonidou, & Katsikeas, ). The studies on CSR can be traced back to Altruism and Warm‐glow effect (Andreoni, ; Andreoni, ).…”
Section: Prior Literaturementioning
confidence: 99%
“…This is in sharp contrast to what pertains in CSR scholarship globally. In a review of CSR and international marketing, only a third of articles reviewed was not anchored on a theory (Eteokleous, et al, 2016). However just as Eteokleous et al (2016) found out, Stakeholder theory was the dominant theory applied.…”
Section: Theoretical Assessmentmentioning
confidence: 99%
“…In a review of CSR and international marketing, only a third of articles reviewed was not anchored on a theory (Eteokleous, et al, 2016). However just as Eteokleous et al (2016) found out, Stakeholder theory was the dominant theory applied. In their review, 21.7% of the articles used the Stakeholder theory but as much as 55.5% applied it in the case of CSR in Ghana.…”
Section: Theoretical Assessmentmentioning
confidence: 99%